Technology Touchpoints: Parenting in the Digital Dystopia - Brady, PhD, MAC, Loretta L. C. (Rowman & Littlefield Publishers, 2022)
Analyzes the influence of technology and social media on human development with parents and families in mind. This is a story about a family coming of age at the same time as smartphones and social media; a multiracial family coming into its own as windows into social injustice opened up before our very screens; and a multi-parent multi-professional family with children living differently depending on which house and which combination of family members happen to be home. While it is a story about a family, it is really the story of technological and global changes unfolding on our doorsteps. While many revile the ascendance of smartphones and social media and the way they suck us into the vortex of cyberspace, there are cultural touchpoints that reflect deeper human and technology development patterns, patterns which we would all do well to understand, no matter whether or how we choose to engage in the ever-innovating digital frontiers. Informed by research and interviews with leaders in policy, human development, ethics, and technology Loretta Brady helps readers understand the complex systemic challenges and findings related to technology and human development. We do not have to hate or fear technology. It is neither friend nor foe. But understanding its impact on our daily lives is paramount to cultivating a healthier relationship both with our digital lives and our real, lived ones.